Preoperative plasmapheresis in patients with Graves' disease intolerant to antithyroid drugs - YAVUZ, DİLEK (WILEY, 2021)
Antithyroid drugs (ATDs) are the mainstay of treatment for Graves' disease with possible detrimental adverse effects. Surgery or radioactive iodine (RAI) ablation is the second choice among the treatment options in cases of non-remission. Normalization of serum thyroid hormone levels as much as possible is required before surgery or RAI to prevent thyrotoxic crisis in patients with uncontrolled Graves' disease. In recent decades, therapeutic plasma exchange (TPE) has been used in the treatment of thyroid storm, drug-induced hepatotoxicity and agranulocytosis, or patients with hyperthyroidism scheduled for emergency surgery. TPE is an effective method to reduce serum FT3, FT4, and TRAB levels in severe hyperthyroid conditions. Although TPE-related complications are rare, the risk of bleeding needs to be taken into consideration in patients who were scheduled for surgery within 24 h after TPE. In terms of reducing intraoperative bleeding, patients can be referred to surgery 24-48 h after TPE, or fresh frozen plasma transfusion can be the preferred treatment for emergency cases.
Keywords: antithyroid drugs; hepatitis; hyperthyroidism; plasma exchange; plasmapheresis